Managing the strategic readiness of industrial companies for digital operations - Mira Holopainen; Juhani Ukko; Minna Saunila (Digital Business, 2022)
This study focused on how the strategic readiness of companies for digital operations is managed. The empirical evidence was derived from case studies on 11 industrial companies. The study's findings show that most of the studied companies face challenges in adjusting their digital operations. In response, we propose that to facilitate strategic readiness for digital operations, companies should find a balance between intuitive and data-based decision making; develop leadership capabilities related to strategic development, technology adoption, and culture creation; find a balance between their own and customers' readiness and willingness to accept digital operations; and increase inter-organizational collaboration in the use of digital technologies to allow for simultaneous upgrading of all partners' strategic readiness for digital operations. This study is among the first to examine the strategic readiness of companies for digital operations by attempting to determine how digital operation can be integrated effectively into daily practice.
Keywords: 650; Digital operation; Strategic readiness; Strategy; Management; Customer; Supply chain